The human body model VIVA+ in far-side collisions: A validation and evaluation study of HBM usage - Johansson Sundblad, Lucas; Wassenius, Philip (My University, 2022)
Crash dummies have been used for many years to evaluate occupant safety. However, with more advanced computers, virtual human body models are becoming increas ingly useful. With this as a background, this project aims to validate the male VIVA+ model, perform identical simulations using a female version of the VIVA+ human body model and subsequently compare these results with the male model. Then, the male VIVA+ model is compared with the WorldSID model in a virtual car environment. Lastly, the VIVA+ model was used to identify if sex dependant behaviour could be observed in a fully modelled car. In order to validate the male VIVA+ model, it was positioned in a generic sled rig which is modelled to replicate the physical sled rig used in a previous study from which the real-world data has also been fetched. When using the VIVA+ model in a safety evaluation, two VIVA+ human body models were placed in a far-side collision setup of a Lynk & Co 01. The human body models’ responses were compared with the responses of two WorldSID models used in the same setup, retrieved from an analysis made at CEVT. Additionally some comparisons between the human body models themselves, placed in a Lynk & Co 01, were performed. A conclusion was drawn that the male VIVA+ model was able to predict the kine matics of a Post Mortem Human Subject in the generic sled rig. The average and median kinematic CORA scores were 0.64 and 0.63, respectively, which is indicating a fair but close to good correlation. In the generic sled simulations, it was disclosed that the simulations had problems with that the seat belt slipped off the occupants’ shoulder to a larger extent than what the experiments showed. It also was concluded that the male and female VIVA+ models have similar kinematic responses in a far side collision where the lowest average kinematic CORA score in a configuration was 0.73. Regarding the evaluation simulations, it was possible to see a resemblance between the male VIVA+ model and the WorldSID model. When comparing the upper body kinematics, Head Injury Criterion values and head acceleration curves between the models, similarities could be seen. Finally, it was concluded that the injuries of the occupants were dependent on their sex. The female VIVA+ model behaved differently compared to the male VIVA+ model when positioned in the driver seat, resulting in lesser injuries for the female model.
Keywords: VIVA+; Human Body Model; Far-side Collision; CORA; Validation; Virtual Testing; WorldSID